Using rich pictures outside of soft systems methodology: a case study analysis. (3rd October 2019) - Berg, Tessa; Bell, Simon; Morse, Steve
The aim of this paper is twofold. Firstly we will highlight how a problem structuring tool, namely the Rich Picture, is being used across many disciplines outside of the soft system methodology which has historically been its home. Secondly, we highlight the controversial presence of non-conforming Rich Picture research and an apparent reluctance to publish from the systems community. In this paper we provide examples of rich picture research used independent from methodology and focus on one case study that uses a novel method of content analysis to appreciate the significance of the stories within their pictures. We demonstrate the theoretical justification and efficacy of an innovation in the assessment of the Rich Picture and its use as a tool to discern issues of importance across mixed groups. We discuss the responses to this work and the implications for innovation within soft OR research. We propose that the Rich Picture should not be seen as sacrosanct just because it derives from a well-established and much respected methodology. We argue that the Rich Picture can be a flexible space where any practitioner can negotiate shared understanding without methodological constraint